The Influence of Nursing Management Education on the Satisfaction Level of Patient Families at Igd Hospital Dr. Haryoto Lumajang: The Influence of Nursing Management Education on the Satisfaction Level of Patient Families at Igd Hospital Dr. Haryoto Lumajang - Ririn Riana; Dodik Hartono; Nafolion Nur Rahmat (Journal of Nursing Care and Biomolecular, 2023)
Introduction: Patient satisfaction is an important indicator that must be considered in health services in the emergency room. This study aims to determine the effect of Nursing Management Education on the Satisfaction Level of Patient Families at Igd Hospital Dr. Haryoto Lumajang. Method:This type of research is an experiment with a One-Group Pretest-Posttest Design. The population of all patients admitted to the Emergency Room (IGD) in January 2023 is 100 cases. The sample in this study were 30 people who were taken by quota sampling. The instrument used was a questionnaire. Data processing with the Mann-Whitney U Test processed with SPSS. Results and Analysis: The results of this study indicate that before getting education, 24 (80%) were dissatisfied, after getting education, 26 (86.7%) were very satisfied. The test results showed that there was an effect of education on nursing education on the level of satisfaction in the emergency room of Dr. Haryoto Lumajang Hospital in 2023 with a value of p = 0.000 <α 0,05. Discus, that is, there is an effect of education on management education on nursing management on the level of satisfaction in the Emergency Room of Dr. Haryoto Lumajang Hospital in 2023.  So that health workers can provide earlier information to patient families about the flow and process of service so as to increase patient family satisfaction.   Keywords: Satisfaction, Education on nursing management